INICIAÇÃO PROFISSIONAL DE PROFESSORAS DE QUÍMICA: CONTRIBUIÇÕES DO ESTÁGIO COMO PESQUISA - Pino, Jose C. D.; Matos, Estéfani C. d.; Ceretta, Jaqueline P.; Frison, Marli D. (Salão do Conhecimento, 2013)
Resumo